Facial Emotion Recognition and Executive Functions in Insomnia Disorder: An Exploratory Study - Almondes, Katie Moraes de; Júnior, Francisco Wilson Nogueira Holanda; Leonardo, Maria Emanuela Matos; Alves, Nelson Torro (Frontiers in Psychology, 2020)
Background Clinical and experimental findings suggest that insomnia is associated with changes in emotional processing and impairments in cognitive functioning. In the present study, we investigate the relationship between facial emotion recognition and executive functioning among individuals with insomnia as well as healthy controls. Method A total of 11 individuals (mean age 31.3 ± 9.4) diagnosed with insomnia disorder and 15 control participants (mean age 24.8 ± 4.6) took part in the study. Participants responded to a facial emotion recognition task which presented them with static and dynamic stimuli, and were evaluated with regard to cognition, sleep, and mood. Results Compared to controls, we found that participants with insomnia performed worse in the recognition of the facial emotion of fear (p = 0.001;ηp2 = 0.549; β = 0.999) and had lower scores in tests of verbal comprehension and perceptual organization (104.00 vs. 115.00, U = 135.5; p = 0.004; Cohen’s, 2013d = 1.281). We also found a relationship between facial emotion recognition and performance in cognitive tests, such as those related to perceptual organization, cognitive flexibility, and working memory. Conclusion Results suggest that participants with insomnia may present some impairment in executive functions as well as in the recognition of facial emotions with negative valences (fear and sadness).